2011
DOI: 10.1093/brain/awr298
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier P-glycoprotein function in Alzheimer's disease

Abstract: A major pathological hallmark of Alzheimer's disease is accumulation of amyloid-β in senile plaques in the brain. Evidence is accumulating that decreased clearance of amyloid-β from the brain may lead to these elevated amyloid-β levels. One of the clearance pathways of amyloid-β is transport across the blood-brain barrier via efflux transporters. P-glycoprotein, an efflux pump highly expressed at the endothelial cells of the blood-brain barrier, has been shown to transport amyloid-β. P-glycoprotein function ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
210
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(224 citation statements)
references
References 67 publications
9
210
1
Order By: Relevance
“…An IF can be employed together with a physiological model in order to calculate physiological parameters, such as metabolic rate of glucose (umol/100 g/min) or blood flow (ml/100 g/min) [250]. The creation of such parametric images can be divided into [208], (E) Anazodo et al [209], (F) Izquierdo-Garcia et al [210], (G) Burgos et al [211], (H) Merida et al [212]; MLAA-based methods: (I) Benoit et al [213]; Segmentation-based methods: (J) Cabello et al [214], (K) Juttukonda et al [215], (L) Ladefoged et al [216].…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…An IF can be employed together with a physiological model in order to calculate physiological parameters, such as metabolic rate of glucose (umol/100 g/min) or blood flow (ml/100 g/min) [250]. The creation of such parametric images can be divided into [208], (E) Anazodo et al [209], (F) Izquierdo-Garcia et al [210], (G) Burgos et al [211], (H) Merida et al [212]; MLAA-based methods: (I) Benoit et al [213]; Segmentation-based methods: (J) Cabello et al [214], (K) Juttukonda et al [215], (L) Ladefoged et al [216].…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…Evidence supporting this role for Pgp includes: (1) observations of Pgp-dependent efflux of Ab in vitro, 59,60 (2) an inverse correlation of Ab deposition and microvascular Pgp expression in human brain tissue, 61 (3) decreased Ab efflux and enhanced Ab deposition in mice that lack Pgp, 62 (4) impaired microvascular Pgp function in a transgenic AD mouse model that is restored by pharmacologic intervention shows corresponding improvement in Ab efflux and reduced Ab deposition, 62,63 and (5) showing Pgp dysfunction in human AD using clinical PET imaging studies. 64 Because of its luminal location, 65 it has been proposed that Pgp facilitates the extrusion of Ab from the endothelial cell into the bloodstream after Ab has been internalized from brain interstitial fluid (ISF) by LRP-1. 63 However, our group has found that under inflammatory conditions, antioxidant treatment that preserves LRP-1 but not Pgp function also preserves Ab efflux.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…Van Assema et al [10] assessed the effects of C1236T, G2677T/A and C3435T single-nucleotide polymorphisms in ABCB1 on BBB P-gp function in healthy subjects and patients with AD. In healthy controls, binding potential did not differ between subjects without and with one or more T present in C1236T, G2677T and C3435T.…”
Section: Journal Ofmentioning
confidence: 99%
“…ATP-binding cassette (ABC) transporters, which are localized on the surface of brain endothelial cells of the BBB and brain parenchyma, affect Aβ transport (flux) across the BBB contributing to the pathogenesis of Alzheimer's disease (AD) [5][6][7][8][9][10][11][12]. One of the clearance pathways of amyloid-β is transport across the BBB via efflux transporters.…”
mentioning
confidence: 99%
See 1 more Smart Citation